Functional interplay between TFIIH and KAT2A regulates higher-order chromatin structure and class II gene expression - Jérémy Sandoz (Nature Portfolio, 2019)
Chromatin structure plays a significant role in the regulation of gene expression. Here the authors show that TFIIH interacts with the histone acetyl transferase KAT2A and recruits the ATAC/hSAGA complexes to chromatin; and that loss of xeroderma pigmentosum group B (XPB) function results in chromatin decondensation and increased gene expression through activation of KAT2A.